2020
DOI: 10.1364/josab.384936
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic degree of coherence of two-qubit states and measures of two-particle quantum correlations

Abstract: Recently, a basis-invariant measure of coherence known as the intrinsic degree of coherence has been established for classical and single-particle quantum states [JOSA B 36, 2765 (2019)]. Using the same mathematical construction, in this article, we define the intrinsic degree of coherence of two-qubit states and demonstrate its usefulness in quantifying two-particle quantum correlations and entanglement. In this context, first of all, we show that the intrinsic degree of coherence of a two-qubit state puts an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Nevertheless, for conceptual clarity, we numerically calculate the inherent error as a function of the intrinsic degree of coherence P of the state in order to directly illustrate how E scales with the mixedness of the state. P is also known as a measure of the purity of the state [51][52][53]. It ranges from 0 to 1, with P = 0 implying a completely mixed state and P = 1 implying a pure state.…”
Section: Measurement Error As a Function Of Mixedness In The Two-phot...mentioning
confidence: 99%
“…Nevertheless, for conceptual clarity, we numerically calculate the inherent error as a function of the intrinsic degree of coherence P of the state in order to directly illustrate how E scales with the mixedness of the state. P is also known as a measure of the purity of the state [51][52][53]. It ranges from 0 to 1, with P = 0 implying a completely mixed state and P = 1 implying a pure state.…”
Section: Measurement Error As a Function Of Mixedness In The Two-phot...mentioning
confidence: 99%
“…However, for certain classes of two-qubit states, there are proposals for quantifying entanglement without reconstructing the entire density matrix [7,8,9,10,11,12,13,14,15]. Moreover, for pure two-qubit states, it has been shown that the reduced density matrix of one of the subsystems contains information about entanglement [16], implying that the two-qubit entanglement can be measured by making measurements on only one of the subsystems without requiring joint measurements [17,18,19,20,21]. Implementing this concept, several groups have measured entanglement of such two-qubit states experimentally by making measurement on only one of the subsystems [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Moreover, for pure two-qubit states, it has been shown that the reduced density matrix of one of the subsystems contains information about entanglement, [16] implying that the two-qubit DOI: 10.1002/andp.202100395 entanglement can be measured by making measurements on only one of the subsystems without requiring joint measurements. [17][18][19][20][21] Implementing this concept, several groups have measured entanglement of such two-qubit states experimentally by making measurement on only one of the subsystems. [18][19][20] This concept has also been used in the context of verifying entanglement in continuous-variable systems.…”
Section: Introductionmentioning
confidence: 99%